PEMBENTUKAN BIDAN ENTERPRENEUR SEBAGAI PELUANG USAHA BIDAN MELALUI PELATIHAN POSTNATAL TREATMENT - Indah Fitri Andini; Susanti, Eva; Esmianti, Farida; Febrina, Lydia (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
Postnatal treatment is a service provided to mothers after giving birth either normally or by cesarean. Postnatal treatment is one of the types of care that is mastered by the alumni of DIII Midwifery Program since it is included in the DIII Midwifery Curriculum at the Midwifery Study Program, Curup Ministry of Health Poltekkes, Bengkulu. Postnatal treatment that has been modified is to do breast care and oxytocin massage with the patient in a position to soak in warm water and be given aromatherapy along with relaxation music. This community service aims to increase the knowledge and skills of students and alumni for entrepreneurship. The solution offered by the implementing team is to increase the knowledge and skills of students and alumni through training on Postnatal Treatment. The entrepreneurial development method passes through three stages, namely entrepreneurial knowledge, entrepreneurial ability, and entrepreneurial mentality. Assistance to students and alumni during the process of implementing activities. Monitoring and evaluation is carried out by the Lecturer Team on students and alumni. This activity resulted in the formation of a new entrepreneurial group, as well as the availability of facilities and infrastructure to support activities such as modules, tools and materials for Postnatal treatment. After the training, there was an increase in the knowledge of alumni and students about Postnatal Treatment.